The Sloan Digital Sky Survey and its Archive - S. Szalay, A.; Kunszt, Peter; Thakar, Anirudha; Gray, Jim; Slutz, Don (ADASS, 1999)
The next-generation astronomy archives will cover most of the universe at fine resolution in many wavelengths. One of the first of these projects, the Sloan Digital Sky Survey (SDSS) will create a 5-wavelength catalog over 10,000 square degrees of the sky. The 200 million objects in the multi-terabyte database will have mostly numerical attributes, defining a space of 100+ dimensions. Points in this space have highly correlated distributions. The archive will enable astronomers to explore the data interactively. Data access will be aided by multidimensional spatial indices. The data will be partitioned in many ways. Small tag objects consisting of the most popular attributes speed up frequent searches. Splitting the data among multiple servers enables parallel, scalable I/O. Hashing techniques allow efficient clustering and pairwise comparison algorithms. Randomly sampled subsets allow debugging otherwise large queries at the desktop. Central servers will operate a data pump that supports sweeping searches that touch most of the data.